2005
DOI: 10.1063/1.1925784
|View full text |Cite
|
Sign up to set email alerts
|

Rapid lateral solidification of pure Cu and Au thin films encapsulated in SiO2

Abstract: Excimer laser melting and lateral resolidification is demonstrated in 200nm thick Cu and Au elemental metal thin films encapsulated between SiO2 layers. Projection irradiation is used to selectively and completely melt lines 3to30μm wide in the metal film—with rapid lateral solidification originating from the unmelted sidewalls of the molten region—resulting in large columnar grains, extending transversely to the middle of the line. Transmission electron microscopy reveals twinning structures and other defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…We have recently used single-pulse excimer laser-induced rapid lateral solidification (RLS) to produce large, very high aspect ratio grains in thin Cu films that are geometrically confined between amorphous silicon oxide capping-and under-layers on Si [3]. Rapid solidification processing of metals and alloys can produce a wide variety of nonequilibrium phases and microstructural configurations that are of interest for technologically useful thin films [2].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently used single-pulse excimer laser-induced rapid lateral solidification (RLS) to produce large, very high aspect ratio grains in thin Cu films that are geometrically confined between amorphous silicon oxide capping-and under-layers on Si [3]. Rapid solidification processing of metals and alloys can produce a wide variety of nonequilibrium phases and microstructural configurations that are of interest for technologically useful thin films [2].…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in localized melting of the copper film in a narrow line of adjustable width [13] as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 97%
“…With the application of excimer laser-induced rapid lateral solidification (RLS) to thin copper films, we have previously demonstrated that large single-crystalline grains can be located at specifically selected sites on a wafer substrate [13]. It involves rapidly and completely melting a localized spot in the metal film on nanosecond timescale, followed by lateral resolidification into the molten pool.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations